Effectiveness of magnetic seizure therapy versus electroconvulsive therapy for major depressive episode in China: protocol for a double-blind, randomized, non-inferiority trial - Zhang, TianHong; He, YongGuang; Liu, Sha; Ju, MingLiang; Yang, YiYi; Zhou, RunChun; Hong, YaWen; Wei, YanYan; Tang, XiaoChen; Zheng, HaoYang; Jia, YuPing; Liu, HaiChun; et al. (Frontiers in Psychiatry, 2025)
Electroconvulsive therapy (ECT) has been a cornerstone in treating Major Depressive Disorder (MDD), demonstrating high efficacy but often limited by cognitive side effects. As an alternative, magnetic seizure therapy (MST) has emerged, offering comparable antidepressant effects with potentially fewer cognitive adverse outcomes. This study aimed to compare the efficacy, safety, and cognitive impact of MST and ECT. This multicenter, double-blind, parallel, non-inferiority randomized clinical trial will be conducted at seven clinical centers. Participants diagnosed with MDD will be randomly allocated to either the ECT or MST group. Each center aims to recruit 30 participants, resulting in a total sample size of 210. The intervention includes 12 sessions over 4 weeks, followed by 12-week follow-up. Assessments (the 24-item Hamilton Depression Rating Scale (HDRS-24), Hamilton Anxiety Scale (HAMA), 8 cognitive tests, Electroencephalography, electrocardiography) occur at baseline, post-sessions 3/6/9/12 (3 hours after each session), and 4-/8-/12-week follow-ups. The primary outcome is the change in HDRS-24 total score from baseline to the 12-week follow-up, which is assessed after the completion of the 12-session acute treatment phase (conducted over 4 weeks) and a subsequent 12-week post-treatment observation period. Randomization and blinding protocols will be strictly followed to ensure unbiased treatment administration and assessment. This trial aims to provide robust evidence that MST is as effective as ECT in reducing depressive symptoms (assessed via HDRS-24) and to confirm its superior cognitive safety, with the Hopkins Verbal Learning Test-Revised as an additional primary outcome to evaluate verbal memory changes. Remaining cognitive measures will serve as secondary outcomes. Exploratory analyses will examine electroencephalography and electrocardiography data to identify potential neurophysiological biomarkers. If successful, this trial could significantly influence clinical practices and improve seizure treatment for patients with MDD.Clinical trial registrationClinicalTrials.gov, identifier NCT06409325.